Rationale and design of SCOPE trial: a prospective, multicentre, open-label, randomised controlled trial to evaluate the overall efficacy and safety of a short-term anticoagulation strategy versus conventional single antiplatelet therapy in patients with severe aortic stenosis without indications for anticoagulation or dual antiplatelet therapy post-transcatheter aortic valve replacement - Yang Wang; Yan Li; Lihua Zhang; Ran Liu; Wei Wu; Yang Li; Huiping Zhang; Stuart Pocock; Xinmin Liu; Zhinan Lu; Taiyang Luo; Liang Guo; et al. (BMJ Open)
Introduction While transcatheter aortic valve replacement (TAVR) has become a well-established standard of care for patients with symptomatic severe aortic stenosis, the optimal antithrombotic strategy post-TAVR remains a subject of debate, particularly in patients without clear indications for anticoagulation or dual antiplatelet therapy. This study aims to investigate the safety and efficacy of rivaroxaban compared with antiplatelet monotherapy in this specific patient population.Methods and analysis This study is designed as a prospective, multicentre, open-label, randomised controlled trial. A total of 454 patients, who have successfully undergone TAVR and do not have indications for long-term anticoagulation or dual antiplatelet therapy, will be consecutively enrolled from seven centres across China. Participants will be randomly assigned to receive either anticoagulation with rivaroxaban (20/15 mg) or conventional antiplatelet therapy (aspirin or clopidogrel) for 1 month. Follow-up evaluations are scheduled at 1, 3, 6 and 12 months post-procedure. After the initial 1-month antithrombotic therapy, the regimen may be adjusted by the investigator based on the patient’s clinical and imaging follow-up results. The primary endpoint is a hierarchical composite of cardiovascular death, first occurrence of myocardial infarction or stroke, first occurrence of life-threatening, disabling or major bleeding, and grade 3 or higher hypo-attenuated leaflet thickening and reduced leaflet motion at 12 months post-TAVR. The win ratio method will be employed to analyse the primary endpoint.Ethics and dissemination This trial was approved by the Ethics Committee of the Beijing AnZhen Hospital. All relevant results will be disseminated through publications in peer-reviewed journals and presentations at conferences.Trial registration number ChiCTR2400087453.